2019
DOI: 10.1093/biolre/ioz080
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of novel monoclonal antibodies for identification of type A spermatogonia in teleosts†

Abstract: We recently established a germ cell transplantation system in salmonids. Donor germ cells transplanted into the body cavity of recipient embryos migrate toward and are incorporated into the recipient gonad, where they undergo gametogenesis. Among the various types of testicular germ cells, only type A spermatogonia (A-SG) can be incorporated into the recipient gonads. Enriching for A-SG is therefore important for improving the efficiency of germ cell transplantation. To enrich for A-SG, an antibody against a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…To identify suitable antibodies for MACS, immunohistochemistry (IHC) was performed on paraffin sections of gonads isolated from 12‐month‐old immature rainbow trout using 11 monoclonal antibodies (nos. 23, 80, 87, 95, 97, 115, 137, 162, 172, 179, and 189) that can recognize the cell surface antigen of rainbow trout germ cells (Hayashi et al, ). A particularly clear and germ‐cell‐specific signal was observed when using antibody nos.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To identify suitable antibodies for MACS, immunohistochemistry (IHC) was performed on paraffin sections of gonads isolated from 12‐month‐old immature rainbow trout using 11 monoclonal antibodies (nos. 23, 80, 87, 95, 97, 115, 137, 162, 172, 179, and 189) that can recognize the cell surface antigen of rainbow trout germ cells (Hayashi et al, ). A particularly clear and germ‐cell‐specific signal was observed when using antibody nos.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, from the antibody library made by directly inoculating ASGs of rainbow trout into mice (Hayashi et al, ), we identified two novel antibodies that can clearly recognize the cell surface antigen of germ cell lineages. Further, by applying antibody no.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations